Oxygen mass transfer in a high solids loading three-phase internal-loop airlift reactor - Teixeira, J. A. (2001)
The way volumetric mass transfer coefficient in a 60 L three-phase internal-loop airlift reactor with an enlarged degassing zone is influenced by the airflowrate (riser superficial gas velocities between 0.01 and 0.5 m/s), solids loading (up to 30% v/v), solids density (1023 and 1048 kg/m³) and the liquid phase properties was studied. The increase of the airflow rate and the introduction of ethanol enhanced the volumetric mass transfer coefficient in the system. The opposite effect was observed with the progressive introduction of solids and a small increase on solids density. Correlations for the volumetric mass transfer coefficient with the riser superficial gas velocity and solids loading were established, for the two solids density and the two liquid-phases.